2009
DOI: 10.1348/096317908x370025
|View full text |Cite
|
Sign up to set email alerts
|

Team climate, climate strength and team performance. A longitudinal study

Abstract: We tested the hypothesis that the relationship between team climate and team performance is moderated by climate strength. The study sample was composed of 155 bank branches, and a two-wave panel design was implemented. We measured four team climate facets (support, innovation, goal achievement and enabling formalization). We obtained two subjective indicators of team performance (ratings provided by team members and by team managers) and a financial indicator of team performance. Seven out of the 12 interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
129
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(142 citation statements)
references
References 55 publications
11
129
1
1
Order By: Relevance
“…As was the case with previous research (González-Romá et al, 2009), there were high intercorrelations of team climate dimensions. Future studies could also evaluate the climate of the teams to supplement the questionnaire items.…”
Section: Limitations and Future Researchsupporting
confidence: 79%
See 1 more Smart Citation
“…As was the case with previous research (González-Romá et al, 2009), there were high intercorrelations of team climate dimensions. Future studies could also evaluate the climate of the teams to supplement the questionnaire items.…”
Section: Limitations and Future Researchsupporting
confidence: 79%
“…Therefore, both frequent communication and a task-oriented team climate were important for performance. Unlike González-Romá et al(2009), we found a relationship between team climate and performance, not only for subjective but also for objective performance.…”
Section: Discussioncontrasting
confidence: 61%
“…risk behavior) to be contingent not only on priority of safety but also pressure for production, thereby enabling us to provide a more complex picture of the interplay between different safety climate dimensions. This is important from a theoretical and practical perspective as our findings ascertain the boundary conditions under which the impact of managerial commitment to safety on employee risk behavior is enhanced or attenuated (for the relevance of moderating effects in climate research, see González-Romá, et al, 2009), which in turn can inform managers about the situations in which their actions and behaviors are particularly influential for reducing employee risk behavior and accidents on site. To our knowledge this is the first study in the safety climate literature to test and find a higher-order interaction between safety climate dimensions, which deserves attention given the difficulty of finding higher-order interactions due to lower statistical power in field research (McClelland and Judd, 1993).…”
Section: Safety Climate Dimensions and Risk Behavior: Interactive Effmentioning
confidence: 91%
“…This study also investigates the possibility that PJ climate level and strength function as contextual moderators, which reinforce the individual-level relationship between PJ perceptions and individual work outcomes. An identical PJ perception level may lead to different attitudes and behavior that are relative to the average level of PJ perceptions within the group and the extent to which members agree on the level of their fairness perceptions (Colquitt et al 2002;González-Romá et al 2009). …”
Section: Research Frameworkmentioning
confidence: 99%